NUTRITION AND FOOD PROCESSING USING THERMAL PROCESS METHODS - Syah Putra, Nico; Alhanannasir , Alhanannasir; Dasir, Dasir; Nur Fadillah, Muhammad (Barkah Publishing, 2025)
Food processing uses thermal processes to maintain product preservation by killing spoilage microbes and pathogens, improving sensory quality, heating products, increasing the digestibility of proteins and carbohydrates, and destroying unnecessary ingredients. Thermal process techniques are preservation techniques that use high temperature and pressure to kill bacteria and pathogens in hermetically packaged foods by applying high heat over 100 degrees Celsius for a certain period of time. To maintain the safety of food products, thermal processing is one of the food processing processes that inactivate microbes in food. Excessive thermal processing can damage nutritional components and reduce the sensory quality of the product. in addition to killing microbes, thermal processing must consider the quality of the final product by minimizing quality damage.